Running position matching for the monitoring bogie and temporal subtraction analysis of derailment coefficient - Yosuke ICHIYANAGI (The Japan Society of Mechanical Engineers, 2019)
The derailment coefficient, which is calculated based on the wheel-rail contact forces, indicates the running safety of a railway vehicle with respect to flange climb derailment. The value of the derailment coefficient changes constantly due to numerous factors associated with the vehicle and track conditions while the vehicle runs on a service line. Therefore, it is desirable to monitor the state of the wheel/rail contact in order to ensure the running safety. Recently, a new monitoring bogie, which can measure the derailment coefficient during commercial operations, has been developed and introduced into some service lines. Large-scale data have been collected by this monitoring bogie. In this paper, the temporal subtraction analysis is carried out for preparing appropriate plan for reducing the derailment coefficient based on these data. In the analysis, the vehicle running position is important for accurate calculation of the difference between two waveforms. However, the vehicle running position contains errors because of the accumulated error of integral calculation of the vehicle velocity. The present paper proposes a method which modifies the running position along track so that the two waveforms are well matched. The proposed method is based on DP matching, and the waveforms of the track irregularity of twist estimated by the monitoring bogie are used in the method. After DP matching, an example of temporal subtraction analysis of the derailment coefficient between two periods is performed. Finally, by using the long-term measurements acquired by the monitoring bogie, the monthly variation of the derailment coefficient for a certain spot on the track is shown as a practical example.